Beneficial Extracardiac Effects of Cardiovascular Medications - Butt, Asra K.; Patel, Jay; Shirwany, Hamid; Mirza, Qasim; Hoover, Jonathan; Khouzam, Rami N. (Current Cardiology Reviews, 2022)
Cardiovascular diseases are the most common cause of death worldwide, with cardiovascular medications being amongst the most common medications prescribed. These medications have diverse effects on the heart, vascular system, as well as other tissues and organ systems. The extra cardiovascular effects have been found to be of use in the treatment of non-cardiovascular diseases and pathologies. Minoxidil is used to manage systemic hypertension with its well-known side effect of hirsutism used to treat alopecia and baldness. Sildenafil was originally investigated as a treatment option for systemic hypertension; however, its side effect of penile erection led to it being widely used for erectile dysfunction. Alpha-1 blockers such as terazosin are indicated to treat systemic hypertension but are more commonly used for benign prostatic hyperplasia and post-traumatic stress disorder. Beta blockers are the mainstay treatment for congestive heart failure and systemic hypertension but have been found useful to help in patients with intention tremors as well as prophylaxis of migraines. Similarly, calcium channel blockers are indicated in medical expulsion therapy for ureteric calculi in addition to their cardiovascular indications. Thiazides are commonly used for treating systemic hypertension and as diuretics. Thiazides can cause hypocalciuria and hypercalcemia. This side effect has led to thiazides being used to treat idiopathic hypercalciuria and associated nephrolithiasis. Spironolactone is commonly utilized in treating heart failure and as a diuretic for edema. It’s well described anti-androgen side effects have been used for acne vulgaris and hirsutism in polycystic ovarian syndrome. This review article discusses how the various extracardiovascular effects of commonly used cardiovascular medications are put to use in managing non-cardiovascular conditions.
Keywords: cardiovascular disease